Răspuns :
120+5*[28-3*(2x-20)]=140⇒28-3*(2x-20)=(140-120)÷5⇒28-3*(2x-20)=4⇒
⇒2x-20=(28-4)÷3⇒2x-20=8⇒2x=28⇒x=28÷2⇒x=14
⇒2x-20=(28-4)÷3⇒2x-20=8⇒2x=28⇒x=28÷2⇒x=14
120+5*[28-3*(2x-140:7)]=140 rezolvam parantezele
120+5*[28*-3*(2x-20)]=140
120+5*(28-6x-60)=140
120+140-30x-300=140 scadem din ecuatie 140
120-30x-300=0
120-30x=300
120-300=30x
30x=-180 x=-180/30 x=-6
120+5*[28*-3*(2x-20)]=140
120+5*(28-6x-60)=140
120+140-30x-300=140 scadem din ecuatie 140
120-30x-300=0
120-30x=300
120-300=30x
30x=-180 x=-180/30 x=-6